Histone acetyltransferase 1 is a succinyltransferase for histones and non‐histones and promotes tumorigenesis. (29th December 2020) - Yang, Guang; Yuan, Ying; Yuan, Hongfeng; Wang, Jiapei; Yun, Haolin; Geng, Yu; Zhao, Man; Li, Linhan; Weng, Yejing; Liu, Zixian; Feng, Jinyan; Bu, Yanan; et al.
Abstract: Lysine succinylation (Ksucc) is an evolutionarily conserved and widespread post‐translational modification. Histone acetyltransferase 1 (HAT1) is a type B histone acetyltransferase, regulating the acetylation of both histone and non‐histone proteins. However, the role of HAT1 in succinylation modulation remains unclear. Here, we employ a quantitative proteomics approach to study succinylation in HepG2 cancer cells and find that HAT1 modulates lysine succinylation on various proteins including histones and non‐histones. HAT1 succinylates histone H3 on K122, contributing to epigenetic regulation and gene expression in cancer cells. Moreover, HAT1 catalyzes the succinylation of PGAM1 on K99, resulting in its increased enzymatic activity and the stimulation of glycolytic flux in cancer cells. Clinically, HAT1 is significantly elevated in liver cancer, pancreatic cancer, and cholangiocarcinoma tissues. Functionally, HAT1 succinyltransferase activity and the succinylation of PGAM1 by HAT1 play critical roles in promoting tumor progression in vitro and in vivo . Thus, we conclude that HAT1 is a succinyltransferase for histones and non‐histones in tumorigenesis. SYNOPSIS: Histone acetyltransferase 1 is a succinyltransferase for histone H3 and PGAM1, thereby contributing to epigenetic regulation and glycolysis to promote tumor growth. HAT1‐catalyzed succinylation of histone H3 at lysine 122 is required for the epigenetic regulation and gene expression in cancer cells. HAT1 succinylates PGAM1 at lysine 99 to stimulate glycolytic flux in cancer cells. HAT1‐mediated succinylation promotes the progression of cancer. Abstract : Histone acetyltransferase 1 is a succinyltransferase for histone H3 and PGAM1, thereby contributing to epigenetic regulation and glycolysis to promote tumor growth.